(untitled) - Sharma, Jaideep (Laxmi Nagar, Delhi, 2001)
Contents of material: 1/ Introduction. 2/ Professional competencies: A Global view. 3/ Educational preparations of LIS professionals. 4/ Curriculum construction. 5/ Library and infomation services in India. 6/ Employer expectations in Indian libraries and information centres. 7/ LIS course contents: Indian scenario. 8/ Professional competencies in India.
Keywords: Information technology,Libraries,Online data processing; Data processing